The Influence Of The Management System And Teacher Performance On The Quality Of Learning At MTs Bilingual Muslimat NU Pucang Sidoarjo - M. Khusni Mubarok; Zakiatur Rofiah (Ridwan Institute, 2023)
School as institution formal, informal and non-formal education requires good management for ensure effectiveness and efficiency of the educational process in order to achieve objective education. Teacher, as factor main in the learning process teach, play role key in reach quality more education good. Quality Education is very dependent on teacher performance, and quality teachers are needed For fulfil demands society. A number draft management explain management as tools, energy, systems, processes, tasks and efforts used For reach objective organization. Function management involve planning, organization, guidance, coordination, supervision, and communication. Performance, on the other hand, involves achievement, ability work, and the results that have been achieved achieved. Teacher performance is very important in reach quality more education good. Therefore that, researchthis entitled